The Danubian lands between the Black, Aegean and Adriatic Seas : (7th century BC-10th century AD) - Tsetskhladze, Gocha R.; Tsetskhladze, Gocha R.; Avram, Alexandru; Avram, Alexandru; Hargrave, James; Hargrave, James (Archaeopress archaeology, 2015)
The themes of this volume are concerned with archaeological, historical, linguistic, anthropological, geographical and other investigations across the vast area (and different regions) through which the Argonauts travelled in seeking to return from Colchis: from the eastern shore of the Black Sea and the mouth of the Danube to the Adriatic. The contributions investigate an extended time period, from Greek colonisation to the end of Antiquity, and different cultural influences involving peoples and states, Greek cities, native peoples, Roman rule and events in Late Roman times. Each particular study contributes to the ground research, helping to create a complete picture of the theoretical level of cultural and political development and interaction of different cultures